Ali Moin's Bhagwa Bhais: Psychological and Social Context - Dr. Saira Irshad; Muhammad Farooq Baig; Dr. Uzma Zareen Nazia (Zaban-o-Adab, 2023)
Ali Moin is a known author of Urdu literature. Many of his books have come to light. He has written many telefilms and drama series so far while hundreds of songs have also come to light. A book containing sketches of Ali Moin was published in "Bhagwa Bhais". The author has skillfully made the ordinary characters scattered around him extraordinary. The sketches written in " Bhagwa Bhais " reflect our social attitudes. The saffron disguise is a garment worn by Hindus in a place of worship that puts their own identity behind them. Ali Moin is familiar with the art of words. Undoubtedly, the collection of sketches " Bhagwa Bhais " can be considered as an invaluable treasure of Urdu literature.